100 primary kids rock Let's Vocab @ STEM - Siri Sarah, Sukor (2019)
Pekan, 10 October- Centre of Modern Languages (CML) has recently received a visit of 100 primary schools’ pupils from Pekan in a program namely Let’s Vocab @ STEM. The program was organized by Industry & Community Network Centre (ICON) in collaboration with CML on 29th August 2019.